Composite electron transport layer, preparation method thereof and perovskite solar cell
By using a composite electron transport layer of the C60/CrF3 layer and SnO2 layer stacked in perovskite solar cells, the problem of poor stability of perovskite solar cells in the prior art is solved, and higher efficiency and stability are achieved.
Patent Information
- Application Number
- CN202411993697.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
The perovskite solar cells prepared by the existing composite electron transport layer have poor stability and are difficult to improve the stability of the battery without losing efficiency.
Using a composite electron transport layer of the C60/CrF3 layer and the SnO2 layer arranged in a stacked manner, the introduction of CrF3 improves the efficiency and stability of perovskite solar cells. CrF3 material has high ductility and excellent conductivity, which can effectively block the migration of halogen ions and water-oxygen permeability in perovskites, and maintain the stability of the perovskite structure.
It improves the efficiency and stability of perovskite solar cells, enhances the air and thermal stability of the battery, and extends the service life of the battery.
Smart Images

Figure CN119836099A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic devices and relates to a composite electron transport layer and a preparation method thereof and a perovskite solar cell. Background Art
[0002] The electron transport layer (ETL) of perovskite solar cells is a key component in the cell structure, and its role is very critical, mainly reflected in the following aspects:
[0003] Electron transport function: The main function of the electron transport layer is to efficiently transport electrons generated by the perovskite light-absorbing layer. When the perovskite layer is exposed to light, electron-hole pairs are generated, and the electron transport layer is responsible for transferring these electrons from the perovskite layer to the electrode, thereby forming an electric current.
[0004] Blocking holes: In addition to transporting electrons, the electron transport layer also needs to effectively block holes and prevent them from entering the electrode, which can reduce the recombination of electrons and holes and improve the efficiency of the battery.
[0005] Interface modification: The electron transport layer can provide a good interface, which helps to improve the crystallization quality of perovskite materials and the overall performance of the device. Through proper interface modification, interface defects and interface state density can be reduced, thereby reducing charge recombination at the interface.
[0006] Band alignment: The band alignment between the electron transport layer and the perovskite layer and the electrode is crucial to the battery performance. Proper band alignment can ensure that electrons are transmitted at the correct energy level without causing electron loss due to large energy level differences.
[0007] Improved stability: The electron transport layer can also improve the long-term stability of the battery. It can protect the perovskite layer by isolating moisture and oxygen from the environment, slowing down material degradation and extending the battery's service life.
[0008] Improving the transport kinetics of charge carriers: By optimizing the material and thickness of the electron transport layer, the transport kinetics of charge carriers can be improved, reducing the resistance during charge transport, thereby improving the overall performance of the battery.
[0009] Commonly used electron transport layer materials include C 60 and SnO2, etc. SnO2 has the advantages of low-temperature preparation and high electron extraction ability. The researchers explored a composite electron transport layer, namely C 60 The composite structure of the SnO2 layer and the SnO2 layer is one of the current mainstream composite electron transport layers, but the stability of the battery prepared by this composite electron transport layer is not very good.
[0010] Therefore, there is an urgent need to provide a solution that can enhance the stability of batteries prepared with a composite electron transport layer without sacrificing efficiency. Summary of the invention
[0011] In view of the shortcomings of the prior art, the present invention aims to provide a composite electron transport layer and a preparation method thereof and a perovskite solar cell. The composite electron transport layer provided by the present invention comprises a stacked arrangement of C 60 / CrF3 layer and SnO2 layer. The introduction of CrF3 can improve the efficiency of perovskite solar cells while improving the stability of the cells, providing a new idea for realizing efficient and stable perovskite solar cells.
[0012] To achieve this object, the present invention adopts the following technical solutions:
[0013] In a first aspect, the present invention provides a composite electron transport layer, wherein the composite electron transport layer comprises a stacked arrangement of C 60 / CrF3 layer and SnO2 layer.
[0014] It should be noted that when the composite electron transport layer is used in perovskite solar cells, C 60 / CrF3 layer is in contact with the perovskite layer.
[0015] The composite electron transport layer provided by the present invention comprises a stacked arrangement of C 60 / CrF3 layer and SnO2 layer, the introduction of CrF3 can improve the efficiency and stability of perovskite solar cells at the same time, this is because: CrF3 material has high ductility and excellent conductivity, its excellent conductivity can make perovskite solar cells achieve higher efficiency; and CrF3 is insoluble in water, alcohol and other substances, and has good insulation properties, making C 60 The / CrF3 layer can block the outward migration of halogen ions in the perovskite, maintain the stability of the perovskite structure, and effectively block the penetration of water, oxygen, etc., thereby effectively improving the stability of perovskite solar cells.
[0016] In the composite electron transport layer of the present invention, CrF3 and C 60 Used together, it can enhance C 60 The electron transport capability of C 60 / CrF3 layer and SnO2 layer cooperate to improve C 60 / CrF3 layer is in interface contact with the back electrode layer.
[0017] Preferably, the C 60 In the / CrF3 layer, C 60The mass ratio of CrF3 to CrF3 is (40-60):1, for example, it can be 40:1, 42:1, 45:1, 48:1, 50:1, 52:1, 55:1, 58:1 or 60:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In the present invention, when C 60 When the mass ratio of C and CrF3 is too small, that is, when the mass ratio of CrF3 is too large, it will hinder the transfer of carriers at the electron transport layer / back electrode interface, resulting in a decrease in current density. 60 If the mass ratio of CrF3 to CrF3 is too large, that is, the mass proportion of CrF3 is too small, the evaporation rate will be uneven, and CrF3 will be randomly located at the top or bottom of the electron transport layer, affecting the experimental repeatability.
[0019] Preferably, the C 60 The thickness of the / CrF3 layer is 10-14nm, for example, it can be 10nm, 10.5nm, 11nm, 11.5nm, 12nm, 12.5nm, 13nm, 13.5nm or 14nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] In the present invention, if C 60 If the thickness of the / CrF3 layer is too small, the electron transport layer will not be fully covered, resulting in an increase in the battery leakage current. 60 If the thickness of the / CrF3 layer is too large, the internal resistance of the battery will increase, resulting in low fill factor and short-circuit current density.
[0021] Preferably, the thickness of the SnO2 layer is 10-20nm, for example, it can be 10nm, 11nm, 11.5nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, the C 60 The thickness ratio of the / CrF3 layer and the SnO2 layer is (1-1.2):1, for example, it can be 1:1, 1.05:1, 1.1:1, 1.15:1 or 1.2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] In a second aspect, the present invention provides a method for preparing the composite electron transport layer according to the first aspect, the preparation method comprising:
[0024] (1) C 60 and CrF3 mixed powder as raw materials, and evaporated to obtain C60 / CrF3 layer.
[0025] (2) In the C 60 A SnO2 layer was prepared on the surface of the / CrF3 layer.
[0026] The present invention uses a blending evaporation strategy to obtain a dense C 60 / CrF3 film, the dense texture can enhance the insulation performance, thereby further improving the stability of perovskite solar cells.
[0027] Preferably, the C 60 In the blended powder of CrF3, C 60 The particle size D50 is 0.02-2μm, for example, it can be 0.02μm, 0.03μm, 0.05μm, 0.08μm, 0.1μm, 0.2μm, 0.5μm, 0.8μm, 1μm, 1.2μm, 1.5μm, 1.8μm or 2μm, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the C 60 In the CrF3 blended powder, the particle size D50 of CrF3 is 0.05-2μm, for example, it can be 0.05μm, 0.08μm, 0.1μm, 0.2μm, 0.5μm, 0.8μm, 1μm, 1.2μm, 1.5μm, 1.8μm or 2μm, etc., but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the C 60 In the blended powder of CrF3, C 60 The mass ratio of CrF3 to CrF3 is (40-60):1, for example, it can be 40:1, 42:1, 45:1, 48:1, 50:1, 52:1, 55:1, 58:1 or 60:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the evaporation rate is For example it could be The above range is not limited to the listed values, and other values not listed within the above range are also applicable.
[0031] In the present invention, when the vapor deposition C 60 When the time of CrF3 layer is fixed, if the evaporation rate is too low, the C 60 / CrF3 layer is too thin; if the evaporation rate is too high, the C 60 / CrF3 layer is relatively thick.
[0032] Preferably, the SnO2 layer is prepared by at least one of atomic layer deposition, sol-gel method, evaporation method and sputtering method, preferably atomic layer deposition method.
[0033] In a third aspect, the present invention provides a perovskite solar cell, wherein the perovskite solar cell comprises the composite electron transport layer described in the first aspect, or a composite electron transport layer prepared by the preparation method described in the second aspect.
[0034] Preferably, the perovskite solar cell comprises a stacked substrate, a front electrode layer, a hole transport layer, a perovskite layer, the composite electron transport layer and a back electrode layer; in the composite electron transport layer, C 60 The SnO / CrF3 layer and the SnO2 layer are sequentially arranged in a direction away from the substrate.
[0035] In the present invention, C in the composite electron transport layer 60 The / CrF3 layer is connected to the perovskite layer, and the SnO2 layer is connected to the back electrode layer.
[0036] Preferably, the perovskite layer is a wide bandgap perovskite layer.
[0037] It should be noted that the wide band gap refers to a band gap energy greater than 1.7 eV.
[0038] In the perovskite solar cell of the present invention, a wide-bandgap perovskite material is preferably used because the CrF3 material in the composite electron transport layer is more compatible with the wide-bandgap perovskite material, can optimize the carrier transport process, reduce interface energy loss, and improve the fill factor (FF).
[0039] The wide bandgap perovskite material may be, for example, methylamine lead iodine bromine, cesium lead iodine or cesium lead bromine.
[0040] The present invention does not specifically limit the material type of the front electrode layer, including but not limited to transparent conductive oxides (TCO), etc. The transparent conductive oxide may be, for example, indium tin oxide (ITO), fluorine-doped tin oxide (FTO) or aluminum-doped zinc oxide (AZO).
[0041] The present invention does not specifically limit the type of material of the hole transport layer, including but not limited to nickel oxide or poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) and the like.
[0042] The present invention does not specifically limit the type of material for the back electrode layer, including but not limited to transparent conductive oxides, metal materials, carbon materials or conductive polymers, etc. The transparent conductive oxide may be, for example, indium tin oxide (ITO) or fluorine-doped tin oxide (FTO), etc. The metal material may be, for example, gold, silver or copper, etc. The carbon material may be, for example, graphite, carbon nanotubes or graphene, etc. The conductive polymer may be, for example, polyaniline, etc.
[0043] Preferably, the thickness of the front electrode layer is 10-150nm, for example, it can be 10nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 50nm, 80nm, 100nm, 120nm or 150nm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, the thickness of the hole transport layer is 10-40 nm, for example, it can be 10 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 25 nm, 30 nm, 35 nm or 40 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the thickness of the perovskite layer is 250-350 nm, for example, it can be 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300 nm, 310 nm, 320 nm, 330 nm, 340 nm or 350 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, the thickness of the back electrode layer is 80-150 nm, for example, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm or 150 nm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] The composite electron transport layer provided by the present invention comprises a stacked arrangement of C 60 / CrF3 layer and SnO2 layer, the introduction of CrF3 can improve the efficiency and stability of perovskite solar cells at the same time, this is because: CrF3 material has high ductility and excellent conductivity, its excellent conductivity can make perovskite solar cells achieve higher efficiency; and CrF3 is insoluble in water, alcohol and other substances, and has good insulation properties, making C 60 The / CrF3 layer can block the outward migration of halogen ions in the perovskite, maintain the stability of the perovskite structure, and effectively block the penetration of water, oxygen, etc., thereby effectively improving the stability of perovskite solar cells.
[0050] In the composite electron transport layer of the present invention, CrF3 and C 60 Used together, it can enhance C 60 The electron transport capability of C 60 / CrF3 layer and SnO2 layer cooperate to improve C 60 / CrF3 layer is in interface contact with the back electrode layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a schematic structural diagram of a perovskite solar cell provided in Application Example 1 of the present invention.
[0052] Figure 2 JV curves of the perovskite solar cells of Application Example 1 of the present invention and Comparative Application Example 1.
[0053] Figure 3 This is a test diagram of the air stability of the perovskite solar cell of Application Example 1 of the present invention and Comparative Application Example 1.
[0054] Figure 4 This is a thermal stability test diagram of the perovskite solar cell of Application Example 1 of the present invention and Comparative Application Example 1.
[0055] Among them, 1-front electrode layer; 2-hole transport layer; 3-perovskite layer; 4-C 60 / CrF3 layer; 5-SnO2 layer; 6-back electrode layer. DETAILED DESCRIPTION
[0056] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0057] Example 1
[0058] This embodiment provides a composite electron transport layer, including a stacked arrangement of C 60 / CrF3 layer and SnO2 layer. 60 In the / CrF3 layer, C 60 The mass ratio of C to CrF3 is 50:1; 60The thickness of the SnO2 layer is 10 nm.
[0059] This embodiment also provides a method for preparing the composite electron transport layer, comprising the following steps:
[0060] The substrate was transferred to a thermal evaporation device and heated to 50:1 C 60 :CrF3 blended powder as raw material, according to The deposition rate was 12 nm to obtain a C 60 / CrF3 layer; then transferred to the ALD equipment, deposited 200 cycles of SnO2 film, thus obtaining a stacked C 60 / CrF3 layer and SnO2 layer.
[0061] Example 2
[0062] The difference between this embodiment and embodiment 1 is that the C 60 In the / CrF3 layer, C 60 The mass ratio of CrF3 is 45:1.
[0063] The remaining parameters remain the same as those in Example 1.
[0064] Example 3
[0065] The difference between this embodiment and embodiment 1 is that the C 60 In the / CrF3 layer, C 60 The mass ratio of CrF3 is 35:1.
[0066] The remaining parameters remain the same as those in Example 1.
[0067] Example 4
[0068] The difference between this embodiment and embodiment 1 is that the C 60 In the / CrF3 layer, C 60 The mass ratio of CrF3 is 65:1.
[0069] The remaining parameters remain the same as those in Example 1.
[0070] Example 5
[0071] The difference between this embodiment and embodiment 1 is that the evaporation rate is adjusted to Make C 60 The thickness of the / CrF3 layer was adjusted to 5 nm.
[0072] The remaining parameters remain the same as those in Example 1.
[0073] Example 6
[0074] The difference between this embodiment and embodiment 1 is that the evaporation rate is adjusted to Make C 60 The thickness of the / CrF3 layer was adjusted to 28 nm.
[0075] The remaining parameters remain the same as those in Example 1.
[0076] Comparative Example 1
[0077] The difference between this comparative example and Example 1 is that the mass of CrF3 is replaced by C 60 , i.e., a composite electron transport layer, comprising a stacked arrangement of C 60 layer and SnO2 layer.
[0078] The remaining parameters remain the same as those in Example 1.
[0079] Application Example 1
[0080] This application example provides a perovskite solar cell, which comprises a glass substrate, and a front electrode layer 1, a hole transport layer 2, a perovskite layer 3, a composite electron transport layer and a back electrode layer 6 stacked in sequence on the glass substrate. Figure 1 shown.
[0081] The front electrode layer 1 is an ITO layer with a thickness of 10 nm; the hole transport layer 2 is a PTAA layer with a thickness of 15 nm; the perovskite layer 3 is a wide bandgap perovskite layer, specifically Cs 0.1 FA 0.9 Pb(I 0.6 Br 0.4 ) 3 layers, with a thickness of 350nm; the composite electron transport layer is the composite electron transport layer provided in Example 1, including a stacked arrangement of C 60 / CrF3 layer 4 and SnO2 layer 5, where C 60 The / CrF3 layer 4 is in contact with the perovskite layer 3; the back electrode layer 6 is an Ag layer with a thickness of 120 nm.
[0082] This application example provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps:
[0083] (1) Place the conductive glass with ITO coating (size 25×25mm) 2 ) were ultrasonically treated in deionized water, ethanol and isopropanol for 10 minutes respectively and then dried. The dried substrate was then treated with oxygen plasma for 10 minutes to optimize the ITO surface work function and improve its wettability to obtain a treated substrate.
[0084] (2) Using a spin coater, 3.5 mg / mL of PTAA chlorobenzene solution was dropped onto the treated substrate and rotated at 4000 rpm for 30 seconds. The substrate was then immediately thermally annealed in an air environment at 120°C for 10 minutes to form a hole transport layer. After cooling to room temperature, the substrate was transferred to a nitrogen-filled glove box.
[0085] (3) In a glove box, a ZUA2000.100 scraper was used on a commercial scraper coater to scrape at room temperature (20°C), and 20 μL of a perovskite precursor solution was dropped on the hole transport layer. The concentration of the perovskite precursor solution was 1 M, and the solvents were DMF and NMP in a volume ratio of 4:1. The solution gap between the substrate and the blade scraper was set to 200 μm, and the coating speed was set to 7 mm / s for scraper coating. After the scraper coating was completed, the newly coated liquid precursor film was immediately transferred to a vacuum chamber, and the vacuum degree was reduced to 1000 Pa within 15 seconds and maintained at this pressure for 90 seconds. Subsequently, the film was taken out of the vacuum chamber and annealed at 100°C for 10 minutes in a glove box to crystallize the film to obtain a substrate with a perovskite layer.
[0086] (4) Using the composite electron transport layer preparation method provided in Example 1, a C 60 / CrF3 layer and SnO2 layer.
[0087] (5) In ALD equipment, about A 120nm thick silver electrode was deposited on the surface of the SnO2 layer at a rate of , and finally a perovskite solar cell was obtained.
[0088] Application Example 2-6
[0089] The difference from Application Example 1 is that the composite electron transport layer provided in Example 1 is replaced by the composite electron transport layers provided in Example 2, Example 3, Example 4, Example 5 and Example 6 respectively.
[0090] The remaining parameters are the same as those in Application Example 1.
[0091] Comparative application example 1
[0092] The difference between this comparative application example and application example 1 is that the composite electron transport layer provided in example 1 is replaced by the composite electron transport layer provided in comparative example 1 in sequence.
[0093] The remaining parameters are the same as those in Application Example 1.
[0094] Performance Testing
[0095] (1) Photoelectric performance test:
[0096] Based on the schemes of Application Example 1 and Comparative Application Example 1, two perovskite solar cells were prepared respectively, and the photoelectric performance of each cell was tested. The specific test conditions are: the effective area is 0.09cm 2 The light source was provided by a Newport Oriel 92192 solar simulator equipped with an AM 1.5G filter with an input power of 100 mW cm -2 .
[0097] Based on the solutions of Application Examples 2-6, a perovskite solar cell was prepared respectively, and tested using the above-mentioned photoelectric performance test method.
[0098] After testing, the short-circuit current density (Jsc), open-circuit voltage (Voc) and fill factor (FF) of the battery were measured, and the photoelectric conversion efficiency (PCE) was calculated from them. The specific values are shown in Table 1.
[0099] According to the measured data, two groups of JV curves of application example 1 and comparative application example 1 were drawn respectively, as shown in Figure 2 As shown in the figure, it can be seen that the photoelectric conversion efficiency of the battery device in Application Example 1 is higher than that in Comparative Application Example 1. This is because CrF3 material is introduced into the composite electron transport layer in Application Example 1 of the present invention, and its excellent conductivity can improve the efficiency of the perovskite solar cell.
[0100] (2) Stability test:
[0101] Based on the solutions of Application Example 1 and Comparative Application Example 1, a perovskite solar cell was prepared respectively, and the following stability tests were performed:
[0102] ①Air stability test:
[0103] The initial PCE of the battery was measured using the same test method as in test (1), and then the battery was placed in air with a relative humidity of 60%, and the photoelectric performance was tested every other day for a total of 15 days.
[0104] Normalize the test results: divide the PCEs of different placement times by the initial PCE to obtain the normalized PCE value.
[0105] Figure 3 The air stability test results of Application Example 1 and Comparative Application Example 1 are shown, and the relationship curves between the normalized PCE values and the placement time of Application Example 1 and Comparative Application Example 1 are shown. It can be seen from the figure that the efficiency decay rate of the battery in Comparative Application Example 1 is significantly accelerated on the 3rd day, and soon reaches below 40% of the initial efficiency, while the efficiency decay of the battery in Application Example 1 with CrF3 is slow, and on the 14th day it still maintains 80% of the initial efficiency, and the air stability is significantly better than the battery in Comparative Application Example 1.
[0106] ② Thermal stability test:
[0107] The initial PCE of the battery was measured using the same test method as in test (1), and then the battery was placed in nitrogen and continuously heated at 85°C. The photoelectric performance was tested after 0 h, 20 h, 40 h, 60 h, 80 h and 100 h.
[0108] Normalize the test results: divide the PCEs of different placement times by the initial PCE to obtain the normalized PCE value.
[0109] Figure 4 The thermal stability test results of Application Example 1 and Comparative Application Example 1 are shown, and the relationship curves between the normalized PCE values and the placement time of Application Example 1 and Comparative Application Example 1 are shown. It can be seen from the figure that the decay rate of the battery in Comparative Application Example 1 is significantly faster than that of the battery in Application Example 1, which indicates that CrF3 helps to improve the thermal stability of perovskite solar cells. The improvement of thermal stability is conducive to avoiding the performance loss of wide-bandgap perovskites caused by the annealing process in the subsequent preparation of stacked devices.
[0110] Depend on Figure 3 and Figure 4 It can be seen that the fluoride CrF3 of the inert metal Cr introduced in the present invention has good insulation properties and can block the outward migration of halogen ions in the perovskite. At the same time, it also acts as a water and oxygen barrier to protect the film from oxidation and corrosion, thereby effectively improving the stability of the perovskite solar cell.
[0111] Table 1
[0112]
[0113] analyze:
[0114] As can be seen from Application Examples 1-2, the present invention introduces CrF3, a fluoride of an inert metal Cr, to modify the electron transport layer. The modified structure is a stacked structure of C 60 / CrF3 layer and SnO2 layer, when the modified composite electron transport layer was applied to single-junction wide-bandgap flip-chip perovskite solar cells, it was found that the perovskite solar cells had excellent efficiency and stability, which was mainly attributed to the good water, oxygen and thermal protection properties of CrF3 for the perovskite film, as well as the excellent conductivity of CrF3 itself, which enhanced the photovoltaic performance of the battery device to a certain extent, and the stability in both air and nitrogen environments was significantly improved.
[0115] It can be seen from Application Examples 1 and 3-4 that when C 60When the mass ratio of C and CrF3 is too small, that is, when the mass ratio of CrF3 is too large, it will hinder the transfer of carriers at the electron transport layer / back electrode interface, resulting in a decrease in the short-circuit current density of the battery. 60 If the mass ratio of CrF3 to CrF3 is too large, that is, the mass proportion of CrF3 is too small, the evaporation rate will be uneven, and CrF3 will be randomly located at the top or bottom of the electron transport layer, causing the battery performance to decline.
[0116] It can be seen from Application Examples 1 and 5-6 that in the evaporation of C 60 / CrF3 layer, if the evaporation rate is too low, the C 60 / CrF3 layer is too thin, resulting in incomplete coverage of the electron transport layer, which leads to increased battery leakage current; if the evaporation rate is too high, the C 60 The / CrF3 layer is too thick, which will increase the internal resistance of the battery, resulting in low fill factor and short-circuit current density.
[0117] It can be seen from Application Example 1 and Comparative Application Example 1 that the photoelectric conversion efficiency of the battery device in Application Example 1 is higher than that in Comparative Application Example 1, which indicates that compared with the traditional C 60 The electron transport layer is a SnO2 layer, and the battery corresponding to the electron transport layer modified by CrF3 in the present invention has a higher photoelectric conversion efficiency.
[0118] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A composite electron transport layer, characterized in that: The composite electron transport layer includes a stacked arrangement of C 60 / CrF3 layer and SnO2 layer.
2. The composite electron transport layer according to claim 1, characterized in that: The C 60 In the / CrF3 layer, C 60 The mass ratio of CrF3 is (40-60):1; Preferably, the C 60 The thickness of the / CrF3 layer is 10-14nm.
3. The composite electron transport layer according to claim 1 or 2, characterized in that: The thickness of the SnO2 layer is 10-20 nm.
4. The composite electron transport layer according to any one of claims 1 to 3, characterized in that: The C 60 / The thickness ratio of CrF3 layer and SnO2 layer is (1-1.2):
1.
5. A method for preparing a composite electron transport layer according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (1) C 60 and CrF3 mixed powder as raw materials, and evaporated to obtain C 60 / CrF3 layer; (2) In the C 60 A SnO2 layer was prepared on the surface of the / CrF3 layer.
6. The preparation method according to claim 5, characterized in that: The C 60 In the blended powder of CrF3, C 60 The particle size D50 is 0.02-2μm; Preferably, the C 60 In the blended powder with CrF3, the particle size D50 of CrF3 is 0.05-2μm; Preferably, the C 60 In the blended powder of CrF3, C 60 The mass ratio of CrF3 is (40-60):
1.
7. The preparation method according to claim 5 or 6, characterized in that: The evaporation rate is 8. The preparation method according to any one of claims 5 to 7, characterized in that: The SnO2 layer is prepared by at least one of atomic layer deposition, sol-gel method, evaporation method and sputtering method, preferably atomic layer deposition method.
9. A perovskite solar cell, characterized in that: The perovskite solar cell comprises the composite electron transport layer according to any one of claims 1 to 4, or a composite electron transport layer prepared by the preparation method according to any one of claims 5 to 8.
10. The perovskite solar cell according to claim 9, characterized in that: The perovskite solar cell comprises a stacked substrate, a front electrode layer, a hole transport layer, a perovskite layer, the composite electron transport layer and a back electrode layer; in the composite electron transport layer, C 60 / CrF3 layer and SnO2 layer are arranged in sequence in a direction away from the substrate; Preferably, the perovskite layer is a wide bandgap perovskite layer; Preferably, the thickness of the front electrode layer is 10-150 nm; Preferably, the thickness of the hole transport layer is 10-40 nm; Preferably, the thickness of the perovskite layer is 250-350 nm; Preferably, the thickness of the back electrode layer is 80-150 nm.
Citation Information
Cited By
A trans-perovskite battery with modified C60 as an electron transport layer and a preparation method thereof
CN122622476A